The Role of Identity of an Animated Character in the Story Line - Soraia Mohamed Sobeih (ARCHive-SR, 2017)
The identity of an animated character means who he really is, or what are the characteristics that would never change? How the character sees himself and how others see him? It includes shape, color, race, beliefs, and choices in life.